The Relationship between Emotional Intelligence and Domain‐Specific and Domain‐General Creativity. (12th August 2018) - Tu, Cuiping; Guo, Jiajun; Hatcher, Ryan C.; Kaufman, James C.
ABSTRACT: The Amusement Park Theory of Creativity, which represents both domain‐specific and domain‐general perspectives of creativity, calls for more research on how individual difference constructs are related to creativity at all ends of the domain‐specificity and general spectrum. Toward this goal, this study examined emotional intelligence (using the Emotional Intelligence Scale) in relationship with both a domain‐general measure (the Abbreviated Torrance Test for Adults) and a domain‐specific measure (Kaufman Domains of Creativity Scale) in a sample of 281 Chinese undergraduates. Although emotional intelligence demonstrated no relationship with divergent thinking, it did positively predict all five domains of creativity on the self‐report measure (ranging from .52 to .77). These findings add to the nuanced relationship between emotional intelligence and creativity and serve as a call for more work of this nature.